Increasing the Local Relevance of Epidemiological Research: Situated Knowledge of Cattle Disease Among Basongora Pastoralists in Uganda - Chenais, Erika; Fischer, Klara (Frontiers in Veterinary Science, 2018)
Cattle disease can have severe negative impacts on the livelihoods of the poor, but still, animal disease management and outreach often remain suboptimal in low-income settings. In a study on Basongora pastoralists in Uganda, we examined local priorities, perceptions and practices regarding cattle disease, in order to improve outreach and disease control advisory work in such contexts. We also investigated how participatory epidemiology can be better equipped for gathering situated knowledge. Empirical material obtained in focus group discussions, interviews, participatory mapping and wealth-ranking was used to perform a thematic, bottom-up analysis. The concepts of situated knowledge and embodied objectivity and insights from participatory research and interdisciplinary dialogue were applied to better embrace local perspectives. Cowdriosis, trypanosomosis, contagious bovine pleuropneumonia, East Coast fever and anthrax were high-priority diseases for participants. Lack of control over the animal health situation and money invested in treatments that did not guarantee recovery were of general importance for disease prioritisation. Participants’ descriptions of diseases sometimes diverged from textbook definitions. Co-infections, chronic and recurring infections and lack of access to formal knowledge were identified as important factors for differences between formal and situated knowledge. Paying attention to situated knowledge and particular context-specific issues such as proximity to a national park proved to be of special relevance for local understanding and experiences with disease. Another factor was the local importance ascribed to number of cattle, rather than production levels. These factors need to be taken into consideration when formulating disease control advice, as does the complex disease landscape. The results reveal the importance of moving research and advice beyond curing ‘knowledge-gaps’ and creating different ways of understanding disease so that situated knowledge can be considered, and disease control improved.